Upper Tithonian ammonites (Himalayitidae Spath, 1925 and Neocomitidae Salfeld, 1921) from Charens (Drôme, France) - Frau, Camille; Bulot, Luc G.; Wimbledon, William A. P.; Ifrim, Christina (Geologica Carpathica, 2016)
Abstract This contribution focuses on the Perisphinctoidea ammonite taxa from the Upper Tithonian at Charens (Drôme, south-east France). Emphasis is laid on five genera that belong to the families Himalayitidae and Neocomitidae. We document the precise vertical range of the index-species Micracanthoceras microcanthum, and a comparative ontogenetic- biometric analysis sheds new light on its range of variation and dimorphism as compared to the bestknown Spanish populations. As herein understood, the lower boundary of the M. microcanthum Zone (base of the Upper Tithonian) is fixed at the FAD of its index species. The faunal assemblages and species distribution of the P. andreaei Zone are rather similar to those described at the key-section of Le Chouet as confirmed by the co-occurrence of the genera Protacanthodiscus, Boughdiriella and Pratumidiscus. New palaeontological evidence supports the view that the basal Neocomitidae Busnardoiceras busnardoi was derived from Protacanthodiscus andreaei in the upper part of the P. andreaei Zone.